Community Empowerment of Pondok Kelor Village Through Shallot Processing Innovation - Muhammad Musfhi El Iq Bali; Nurhayati Nurhayati; Nadifatul Mukarromah Nadifatul Mukarromah; Indah Zahrotul Awliya; St. Nur Halisah; Miladiana Miladiana; Agustina Dewi (Communautaire: Journal of Community Service, 2022)
Shallots farming in Pondok Kelor Village, Paiton District,Probolinggo Regency is a potential that has opportunities forfarmers in the future, many farmers in the village plantshallots as a superior crop that gives high expectations fromtheir agricultural business. Based on these assets andpotential, it is necessary to have an innovation from theprocessing of shallot agricultural products to increase theincome of the shallot harvest. The form of service that will becarried out is community empowerment in makingprocessed red onions into ready-to-eat food products,namely Brambang Chips. Brambang chips are processedproducts that are made, namely a chip product made fromshallots. With the development of this processed product,shallot farmers can find out the potential and manage theirassets optimally so that they are able to support theachievement of the economic welfare of the community inthe environment.